Preoperative medical treatment in Cushing's syndrome: frequency of use and its impact on postoperative assessment: data from ERCUSYN. Issue 4 (April 2018) - Valassi, Elena; Franz, Holger; Brue, Thierry; Feelders, Richard A; Netea-Maier, Romana; Tsagarakis, Stylianos; Webb, Susan M; Yaneva, Maria; Reincke, Martin; Droste, Michael; Komerdus, Irina; Maiter, Dominique; et al.
Abstract : Background: Surgery is the definitive treatment of Cushing's syndrome (CS) but medications may also be used as a first-line therapy. Whether preoperative medical treatment (PMT) affects postoperative outcome remains controversial. Objective: (1) Evaluate how frequently PMT is given to CS patients across Europe; (2) examine differences in preoperative characteristics of patients who receive PMT and those who undergo primary surgery and (3) determine if PMT influences postoperative outcome in pituitary-dependent CS (PIT-CS). Patients and methods: 1143 CS patients entered into the ERCUSYN database from 57 centers in 26 countries. Sixty-nine percent had PIT-CS, 25% adrenal-dependent CS (ADR-CS), 5% CS from an ectopic source (ECT-CS) and 1% were classified as having CS from other causes (OTH-CS). Results: Twenty per cent of patients took PMT. ECT-CS and PIT-CS were more likely to receive PMT compared to ADR-CS ( P < 0.001). Most commonly used drugs were ketoconazole (62%), metyrapone (16%) and a combination of both (12%). Median (interquartile range) duration of PMT was 109 (98) days. PIT-CS patients treated with PMT had more severe clinical features at diagnosis and poorer quality of life compared to those undergoing primary surgery (SX) ( P < 0.05). Within 7 days of surgery, PIT-CS patients treated with PMT were more likely to have normal cortisol ( P < 0.01) and a lower remission rate ( P < 0.01). Within 6 months of surgery, no differences in morbidity or remission rates were observed between SX and PMT groups. Conclusions: PMT may confound the interpretation of immediate postoperative outcome. Follow-up is recommended to definitely evaluate surgical results.